2011
DOI: 10.1186/gb-2011-12-9-r93
|View full text |Cite
|
Sign up to set email alerts
|

Effective detection of rare variants in pooled DNA samples using Cross-pool tailcurve analysis

Abstract: Sequencing targeted DNA regions in large samples is necessary to discover the full spectrum of rare variants. We report an effective Illumina sequencing strategy utilizing pooled samples with novel quality (Srfim) and filtering (SERVIC4E) algorithms. We sequenced 24 exons in two cohorts of 480 samples each, identifying 47 coding variants, including 30 present once per cohort. Validation by Sanger sequencing revealed an excellent combination of sensitivity and specificity for variant detection in pooled samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…We have previously observed that many false positive variant calls can be efficiently and specifically removed by applying two pre-filters determined by the proportion of base call from opposing strands and by inter-variant proximity [ 22 ]. Firstly, during read alignment, sequenced reads may be aligned to either the positive (Crick) or negative (Watson) strand.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously observed that many false positive variant calls can be efficiently and specifically removed by applying two pre-filters determined by the proportion of base call from opposing strands and by inter-variant proximity [ 22 ]. Firstly, during read alignment, sequenced reads may be aligned to either the positive (Crick) or negative (Watson) strand.…”
Section: Resultsmentioning
confidence: 99%
“…A large portion of the variants in dbSNP that have a MAF > 0.73% are re-discovered and removed given the sample size of our study, thus explaining why our filter outperforms the “Non-Clinical” dbSNP filter. Additionally, we have previously observed that false positive variant calls occur in parallel in multiple samples due to systematic errors in preparation or sequencing of the same library [ 22 ]. As an added advantage, our strategy removes these variants by comparing samples prepared in the same library, a process of self-neutralizing these reoccurring systematic errors.…”
Section: Resultsmentioning
confidence: 99%
“…We used next-generation technology to sequence all 120 protein coding exons (including alternative exons) of NRG1 and NRG3 , the NRG receptor gene ERBB4 , the BACE1 gene, which encodes β-secretase enzyme, and the six genes that encode the components of the γ-secretase multiprotein complex ( PSEN1 , PSEN2 , PSENEN , NCSTN , APH1A and APH1B ), totaling 38.9 kb of genomic sequence. We sequenced amplified DNA from pools of four subjects (12 pools in total) following the procedures reported by Niranjan et al 50 with minor modifications. We aligned the reads to the reference human genome sequence (hg19 build) using the Bowtie alignment program, 51 and subsequently processed, sorted and indexed using SAMtools.…”
Section: Methodsmentioning
confidence: 99%
“…We identified multiple missense mutations clustered at PDZ4-6 of GRIP1 in a cohort of patients with autism [28,29]. These autism-associated mutations showed a gain-of-function effect manifesting an increase in binding with GluA2 in yeast-two-hybrid assay and an accelerated recycling of GluA2 in hippocampal neurons [28].…”
Section: Introductionmentioning
confidence: 99%